Aktivitas Digital PR Melalui Instagram@Panensegar - Maulana, Abim; Tresnawati, Betty (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the implementation of the POAC (Planning, Organizing, Actuating, Controlling) concept developed by George R. Kelly in the publication activity of the wholesale farmer's harvest program through the Instagram social media @panensegar. The research method used in this research is descriptive qualitative method. This study has four findings as follows. First, at the planning stage the management of digital PR is carried out in the form of formulating objectives to determining the media used. Second, management by the Chief Executive Officer for the content and media used by Panen Segar, namely Instagram. Third, monitoring the publication activities of the farmers' wholesale harvest program through Instagram @panensegar. Supervision is in the form of research on the insight feature in the Instagram application which can be accessed by all users who know the account password. Fourth, Panen Segar uses internal and external assessments as a kind of control for publication-related activities.